An uncertain future: Effects of ocean acidification and elevated temperature on a New Zealand snapper (Chrysophrys auratus) population. (October 2020) - Parsons, Darren M.; Bian, Richard; McKenzie, Jeremy R.; McMahon, Shannon J.; Pether, Steven; Munday, Philip L.
Abstract: Anthropogenic CO2 emissions are warming and acidifying Earth's oceans, which is likely to lead to a variety of effects on marine ecosystems. Fish populations will be vulnerable to this change, and there is now substantial evidence of the direct and indirect effects of climate change on fish. There is also a growing effort to conceptualise the effects of climate change on fish within population models. In the present study knowledge about the response of New Zealand snapper to warming and acidification was incorporated within a stock assessment model. Specifically, a previous tank experiment on larval snapper suggested both positive and negative effects, and otolith increment analysis on wild snapper indicated that growth may initially increase, followed by a potential decline as temperatures continue to warm. As a result of this uncertainty, sensitivity analysis was performed by varying average virgin recruitment (R0 ) by ±30%, adult growth by ±6%, but adjusting mean size at recruitment by +48% as we had better evidence for this increase. Overall adjustments to R0 had the biggest impact on the future yield (at a management target of 40% of an unfished population) of the Hauraki Gulf snapper fishery. The most negative scenario suggested a 29% decrease in fishery yield, while the most optimistic scenario suggested a 44% increase. While largely uncertain, these results provide some scope for predicting future impacts on the snapper fishery. Given that snapper is a species where the response to climate change has been specifically investigated, increasing uncertainty in a future where climate change and other stressors interact in complex and unpredictable ways is likely to be an important consideration for the management of nearly all fish populations. Highlights: Modelling suggests the effect of climate change on snapper populations is uncertain. Impacts range from a 29% reduction to a 44% increase in fishery yield. These impacts are most likely mediated via impacts on recruitment.